2022
DOI: 10.3390/cancers14061582
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cognitive Impairment on Treatment Toxicity, Treatment Completion, and Survival among Older Adults Receiving Chemotherapy: A Systematic Review

Abstract: Cognitive impairment (CI) is common among older adults with cancer, but its effect on cancer outcomes is not known. This systematic review sought to identify research investigating clinical endpoints (toxicity risk, treatment completion, and survival) of chemotherapy treatment in those with baseline CI. A systematic search of five databases (inception to March 2021) was conducted. Eligible studies included randomized trials, prospective studies, and retrospective studies in which the sample or a subgroup were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…For example, a review of studies by Sattar et al examining pretreatment cognitive impairment on chemotherapy toxicity revealed mixed findings and highlighted that such studies often exclude PLWD versus people who have milder cognitive impairment. 90 Consequently, Sattar et al concluded that, to date, research has not adequately explored the effect of baseline cognition or cognitive impairment, particularly dementia. 90 Concerning other complications, single studies have found that dementia is associated with an increased risk of fractures after hormone therapy for prostate cancer, 91 but not with an increased rate of systemic or local wound complications after breast cancer surgery.…”
Section: Cancer Treatment-related Complications Including Dementia Wo...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a review of studies by Sattar et al examining pretreatment cognitive impairment on chemotherapy toxicity revealed mixed findings and highlighted that such studies often exclude PLWD versus people who have milder cognitive impairment. 90 Consequently, Sattar et al concluded that, to date, research has not adequately explored the effect of baseline cognition or cognitive impairment, particularly dementia. 90 Concerning other complications, single studies have found that dementia is associated with an increased risk of fractures after hormone therapy for prostate cancer, 91 but not with an increased rate of systemic or local wound complications after breast cancer surgery.…”
Section: Cancer Treatment-related Complications Including Dementia Wo...mentioning
confidence: 99%
“…90 Consequently, Sattar et al concluded that, to date, research has not adequately explored the effect of baseline cognition or cognitive impairment, particularly dementia. 90 Concerning other complications, single studies have found that dementia is associated with an increased risk of fractures after hormone therapy for prostate cancer, 91 but not with an increased rate of systemic or local wound complications after breast cancer surgery. 17 Insufficient research has examined cancer treatment-related effects on BPSD and on dementia-related symptoms and functioning more broadly.…”
Section: Cancer Treatment-related Complications Including Dementia Wo...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, BCR may be inadequately communicated with breast cancer survivors, such that survivors are unaware of (1) their recurrence risk, (2) factors that influence risk, and (3) health behaviors to decrease their risk [ [22] , [23] , [24] ]. Along with challenges of limited clinician time restricting communication, patients may not remember that risk information was being communicated (perhaps due to the trauma of diagnosis [ 25 , 26 ], chemotoxicity [ 27 ], or challenges with numeracy [ 28 ] or health disparities [ 29 ]). Adequate physician-patient communication about recurrence is vital to quality of life [ 30 ] and to informed decision-making about survivorship care [ 21 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GA can predict cancer treatment toxicity, treatment completion, and survival. The prognostic impact of each GA-domain and their evolution during cancer remain to be clarified and give rise to numerous research works [ 6 , 7 , 8 , 9 ].…”
mentioning
confidence: 99%